Biflavones and Furanone Glucosides from Zabelia tyaihyonii. Issue 10 (October 2015) - Jang, Hari; Lee, Jin Woo; Jin, Qinghao; Kim, Soo‐Young; Lee, Dongho; Hong, Jin Tae; Kim, Youngsoo; Lee, Mi Kyeong; Hwang, Bang Yeon
Abstract Two new biflavones, (aR)‐3′‐methoxycupressuflavone (1) and (aR)‐3′, 3′′′‐dimethoxycupressuflavone (2), and two new furanone glucosides, zabeliosides A and B (3 and 4, resp.), along with two known biflavones, cupressuflavone (5) and amentoflavone (6), were isolated from the leaves of Zabelia tyaihyonii. The structures of the new compounds were elucidated by 1D‐ and 2D‐NMR, HR‐ESI‐MS, and circular dichroism.